Simplify: cos x cos x

----- + -----
sec x-1 sec x+1

1 answer

is that
cosx/(secx - 1) + cosx/(secx + 1) ???

of so, then using a common denominator , ...
(cosx(secx + 1) + cosx(secx - 1)) / (sec^2 x - 1)
= cosx(2secx)/tan^2x
= cosx(2/cosx) ( cos^2x/sin^2x
= 2cot^2 x
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions